The Effect of Credit Risk Management on the Financial Performance of Banks Listed on the IDX - Graficka Dea Evoney; Margaretha, Farah (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the influence of credit risks such as non-performing loans (NPL), expected credit loss provision (ECL), and loan-to-deposit ratio (LDR) on the bank's financial performance as measured by the return on assets (ROA). This study uses purposive sampling as a sampling method. The sample taken is a conventional commercial bank company listed on the Indonesia Stock Exchange (IDX) for a five-year period from 2018 – 2022. Data were collected from 44 banks and analyzed using descriptive statistics and fixed-effect models for hypothesis testing. Data testing was carried out by panel data regression analysis method using E-views 9.0. The results of this study show that (1) NPL has a negative effect on ROA. An increase in NPLs will lower ROA, and vice versa. (2) ECL has a negative effect on ROA. An increase in ECL will lower ROA, and vice versa. (3) LDR has no effect on ROA. Banks need to maintain low NPLs and ECLs to maximize the bank's financial performance. Based on this research, banks are advised to conduct a careful credit evaluation before a loan application is approved. The researcher recommends that further research can add other independent variables that affect the financial performance of banks in order to get more accurate and general results.